Lipid nanocapsules for dermal application: A comparative study of lipid-based versus polymer-based nanocarriers - Abdel-Mottaleb, Mona M.A.; Neumann, Dirk; Lamprecht, Alf (European journal of pharmaceutics and biopharmaceutics, 2011)
Lipid nanocarriers are efficient transdermal drug delivery systems while polymeric nanoparticles are better suited for local effects on the skin. Lipid nanocapsules (LNC) are colloidal carriers providing controlled release profiles and improved bioavailability for many drug substances and diverse administration routes. However, they have not been explored before for transdermal application. Here, we study the behavior of LNC as a transdermal drug delivery system using ibuprofen as a model drug. A comparison to other lipid nanocarriers such as solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) and polymeric nanocarriers has been made. It was found that LNC could increase the flux rate of ibuprofen 21.9 ± 0.5 compared to 5.8 ± 0.4 μg/cm 2 h in case of drug solution. Similar flux rates were obtained for SLN and NLC with average values of 22.9 ± 0.5 and 22.5 ± 2.0 μg/cm 2 h, respectively. On the other side, comparison to polymeric nanoparticles showed that the polymer-based carriers of the same particle size had lower permeation-enhancing effect with a flux rate of 10.62 ± 1.84 μg/cm 2 h. Polymeric carriers had fourfold higher accumulation in the skin compared to that of the LNC and twice the accumulation of SLN and NLC. These results would suggest that the LNC can be considered as efficient as SLN and NLC for the transdermal drug delivery while polymeric nanoparticles are more suitable for localized drug delivery to the skin.